Brazilian high-level men's volleyball : characterization of the attack performed by the opposite player - Conti, Gustavo (Array, 2018)
The present study aimed to characterize and differentiate between the predictive factors of the attacks performed by the opposite player from positions 1 and 2. The sample consisted of the observation records of 142 volleyball games of the Brazilian Men’s Super-League season 2014/2015, totaling 8,010 actions of reception, setting and attack, with 5,965 actions from position 2 and 2,045 from position 1. The analysis of the predictive factors of the opposite player’s attack, according to the position of the attack, showed that the attacks from position 2 are more likely to occur after reception B (OR:1.317), in either diagonal (OR:1.302) or parallel (OR: 1.548), and to result in blocking of the attack (OR:1.496). On the other hand, attacks performed from position 1 are more likely to occur after receiving A (OR:0.458) resulting in a point (OR:0.709). Thus, situational constraints influenced the predictive factors of the opposite player’s attack, according to the attacking position